2005
DOI: 10.1073/pnas.0503899102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the light chain-binding domain of myosin V

Abstract: Myosin V is a double-headed molecular motor involved in organelle transport. Two distinctive features of this motor, processivity and the ability to take extended linear steps of Ϸ36 nm along the actin helical track, depend on its unusually long light chainbinding domain (LCBD). The LCBD of myosin V consists of six tandem IQ motifs, which constitute the binding sites for calmodulin (CaM) and CaM-like light chains. Here, we report the 2-Å resolution crystal structure of myosin light chain 1 (Mlc1p) bound to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(125 citation statements)
references
References 47 publications
5
119
1
Order By: Relevance
“…By contrast, a ''straight-legged'' model was favored, based on FIONA analysis of processively walking myosin V (30). This latter observation is consistent with the crystal structure of the second and third IQ motifs from yeast myosin V with bound light chains (MLC1p), which showed a straight helix, and few interactions between light chains, despite a 25-aa spacing (27).…”
Section: The Semi-open Lobe Conformation and Its Specificity Of Recogsupporting
confidence: 49%
See 1 more Smart Citation
“…By contrast, a ''straight-legged'' model was favored, based on FIONA analysis of processively walking myosin V (30). This latter observation is consistent with the crystal structure of the second and third IQ motifs from yeast myosin V with bound light chains (MLC1p), which showed a straight helix, and few interactions between light chains, despite a 25-aa spacing (27).…”
Section: The Semi-open Lobe Conformation and Its Specificity Of Recogsupporting
confidence: 49%
“…The site showing the most significant deviation from the consensus sequence is IQ6 (IQxxxRGxxxR is replaced by IQxxxRRxxxK), but this may not affect calcium sensitivity. It has been shown that the presence of a bulky side chain at position 7 and/or the absence of a positively charged residue at position 11 causes the N-lobe of CaM (or a specific light chain) to be in an unusual extended conformation that does not interact with the IQ motif (27). Such unbound N-lobes have been proposed to engage in protein-protein interactions.…”
Section: The Semi-open Lobe Conformation and Its Specificity Of Recogmentioning
confidence: 99%
“…Alternatively, Ca 2ϩ -induced activation is initiated from the CaM in IQ2 and transduced to the CaM in IQ1 through interaction between these CaMs as shown in the crystal structure of light chain-binding domain of myosin V (29,31). It appears that activation of ATPase activity of myosin Va by high Ca 2ϩ is correlated with Ca 2ϩ -induced dissociation of CaM from a single specific IQ motif (32).…”
Section: Mechanism For Inhibition Of the Motor Domain Atpase By The Gtdmentioning
confidence: 99%
“…The myosin-1C IQ motifs also lack the sequence features necessary to bind the N-lobe of apo-CaM. The glycine and arginine residues in the C-terminal GXXXR portion of conventional IQ motifs play important roles in binding the N-lobe of CaM, and both are missing in the myosin-1C IQ motifs (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The M1C-IQ1 and M1C-IQ2 motifs are each 18 residues in length and thus are considerably shorter than conventional IQ motifs that bind apo-CaM or CaM-related LCs, which typically include 23-25 amino acids (31). When the C-lobe of apo-CaM is modeled in place of MlcC on the M1C-IQ.1.2 fragment, there are substantial steric clashes between the two N-lobes that could preclude their binding to the IQ motifs (Fig.…”
Section: Discussionmentioning
confidence: 99%